The library as a socio-cultural institution: a study at the State Public Library of Alagoas (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
: Bringing into focus discussions about cultural status and the defense of democracy, this article aims to identify elements present in the Graciliano Ramos State Public Library that may characterize it as a socio-cultural institution. The research is descriptive in nature, using field research to carry out the analyses, adopting a qualitative perspective in the process of constructing the syntheses. For the theoretical foundation, bibliographic and documentary research was used. As a result, the Graciliano Ramos State Public Library promotes its social mission within its possibilities, contributing to cultural citizenship.
Keywords: information units; public library; culture